The effect of rhizobia in improving the protective mechanisms of wheat under drought and supplementary irrigation conditions - Najafi Vafa, Zahra; Sohrabi, Yousef; Mirzaghaderi, Ghader; Heidari, Gholamreza (Frontiers in Sustainable Food Systems, 2022)
The effect of bio-fertilizers containing beneficial soil microorganisms on wheat protection mechanisms under dryland conditions and supplementary irrigation was studied in a split-split plot in a randomized complete block design during the two cropping years 2017-2018 and 2018-2019. Irrigation treatments as the main factor (without irrigation or dryland, one irrigation in the booting stage and twice in booting and spiking stages), wheat cultivars (Sardari and Sirvan) as the second factor, and application of bio-fertilizers in eight levels (including Mycorrhiza, Nitrozist + Phosphozist, Seaweed extract, application of Mycorrhiza + Nitrozist and Phosphozist, Seaweed extract + Nitrozist and Phosphozist, Mycorrhiza + Seaweed extract, Mycorrhiza + Nitrozist and Phosphozist control) as the third factor were considered. The study showed that in both years, bio-fertilizers application with once and twice supplementary irrigation levels increased the leaf relative water content (RWC) and soluble proteins content (SPC), and lack of irrigation increased the malondialdehyde (MDA) content. In both years, bio-fertilizers, especially their combinations, increased the amount and activity of enzymatic and non-enzymatic antioxidants, including peroxidase (POD), superoxide dismutase (SOD), phenol (Phe), flavonoid (Fla), and anthocyanin (Anth). Also, it increased the oxygen free radicals inhibition or 2-2-Diphenyl picryl hydrazyl (DPPH) and cleared the active oxygen species. This study showed that the lowest amount of malondialdehyde (MDA) was obtained in wheat under two times irrigation with averages of 3.3909 and 3.3865 µmol g-1 FW. The lack of irrigation increased the amount of this trait (with an average of 1.7416 and 1.8974 µmol g-1 FW). The results indicated a significant positive relationship between non-enzymatic and enzymatic antioxidants such as Phe, Fla, Anth, DPPH, POD, and SOD enzymes and their role in improving stress under dryland conditions, especially in the Sardari variety. Biological fertilizers (Mycorrhiza + Nitrozist and Phosphozist + Seaweed extract) increased wheat yield compared to the control. Consequently, Mycorrhiza + Nitrozist and Phosphozist + Seaweed extract improved grain yield by 8.04% and 6.96% in the first and second years, respectively. Therefore, appropriate combinations of microorganisms, beneficial biological compounds, and supplementary irrigation can reduce the adverse effects of drought stress in arid and semi-arid regions.